Antioxidant, cholinesterase and tyrosinase inhibitory activities of calophyllum symingtonianum and calophyllum depressinervosum - Aminudin, Nurul Iman; Ahmad, Farediah; Bakhtiar, M. Taher (2015)

(untitled)
Calophyllum is a pan-tropical genus belongs to the Guttiferae family and locally known in Malaysia as “bintangor”. There has been a continual interest to further investigate the phytochemistry of Calophyllum spp since this genus is a rich source of active secondary metabolites. In this study, antioxidant, cholinesterase and tyrosinase enzymatic inhibition activities of leaves and heartwood of Calophyllum symingtonianum, and the bark of Calophyllum depressinervosum were conducted. All extracts were tested for their total phenolic content and antioxidant activities by DPPH radical scavenging and β-carotene bleaching. Cholinesterase inhibition by Ellman’s method and tyrosinase inhibition using L-DOPA as a substrate were also tested. All methanol extracts were found to exhibit strong DPPH radical scavenging effects. The methanol extract of C. depressinervosum bark showed 95.08% inhibition of β-carotene bleaching and 78.46% inhibition against butyrylcholinesterase (BChE). All extracts showed moderate inhibition towards tyrosinase activity with an IC50 of more than 100 μg/mL.